2014
DOI: 10.1182/blood-2013-04-496760
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase 1 is expressed in murine erythroid cells where it controls the level of regulatory heme

Abstract: Key Points• Heme oxygenase-1 levels increase during erythroid differentiation.• Heme oxygenase-1 actively participates in maintaining appropriate hemoglobinization rates.Heme is essential for the function of all aerobic cells. However, it can be toxic when it occurs in a non-protein-bound form; cells maintain a fine balance between heme synthesis and catabolism. The only physiological mechanism of heme degradation is by heme oxygenases (HOs). The heme-inducible isoform, HO-1, has been extensively studied in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 49 publications
(52 reference statements)
5
33
0
Order By: Relevance
“…20 HO-1 overexpression in MEL cells impaired hemoglobin synthesis, while fetal liver cells from HO-1 knock-out embryos contained more hemoglobin. We showed that HO-1 is induced in both Flvcr1a-and Flvcr1a/1b-deficient cells and animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 HO-1 overexpression in MEL cells impaired hemoglobin synthesis, while fetal liver cells from HO-1 knock-out embryos contained more hemoglobin. We showed that HO-1 is induced in both Flvcr1a-and Flvcr1a/1b-deficient cells and animals.…”
Section: Discussionmentioning
confidence: 99%
“…1,21,22 Recently, Garcia-Santos et al introduced the concept of a free heme pool also for erythroid cells and demonstrated that HO-1 is involved in its control, thus regulating hemoglobinization. 20 In fact, in erythroid cells, free heme is thought to increase during terminal maturation and control the expression of globin genes. Premature expansion of the regulatory heme pool is expected to result in premature erythroid differentiation while, contrariwise, a contraction of the heme pool should result in inappropriate hemoglobin production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The BLVRB gene product BV IXb reductase and its structurally distant homolog BLVRA (BV IXa reductase) function downstream of heme oxygenase(s)-1 (inducible HMOX1) and -2 (constitutive HMOX2) within the heme degradation pathway to catalyze reduction of BV IXa (or IXb) tetrapyrrole(s) to the potent antioxidants bilirubin (BR) IXa and IXb. 16,26 We studied expression patterns of the 4 heme degradation pathway genes along erythroid/MK (E/Meg) lineage development using data extracted from platelet 14 and genetic atlases.…”
Section: Distinct Patterns Of Blvrb Expression During Erythroid/mk Spmentioning
confidence: 99%
“…There is growing evidence that the tight control of intracellular heme levels is accomplished by coordination of heme synthesis, degradation, and trafficking between intracellular compartments. 2 In contrast to the well-characterized biochemistry of heme synthesis and degradation, the mechanisms of heme transport remain somewhat obscure.…”
mentioning
confidence: 99%